Enhancing Students’ Vocabulary Mastery Through Dabble Game At The Eleventh Grade of MAS AL-Washliyah 22 Tembung - Lubis, Aisyah; Tri Widya Sandika (Journal of Applied Linguistics, 2025)
This study aimed to improve students’ vocabulary mastery through the use of the "dabble" game. It was conducted using a classroom action research method, which was carried out in two cycles. Cycle I involved three meetings, while Cycle II also had three meetings. The research was conducted with the students of class XI-B at Madrasah Aliyah Swasta Al-Washliyah 22 Tembung, which had 36 students in total. Data collection involved both quantitative and qualitative methods. The quantitative data consisted of the students' scores, while the qualitative data was collected through observation sheets and diary notes. The results showed that students' vocabulary scores improved with each test. For example, the mean score in the initial "Orientation" test was 50.66, but by the first test in Cycle I, the mean score increased to 70.33. By the end of Cycle II, in the final test (Test II), the mean score rose further to 86.08, demonstrating steady progress. Additionally, based on the observation sheets and diary notes, it was found that the teaching-learning process proceeded smoothly, with no significant disruptions. This indicates that the implementation of the dabble game in the classroom contributed positively to enhancing the students' English vocabulary mastery, suggesting that game-based learning can be an effective strategy for improving language skills. Keywords : Enhancing, Vocabulary Mastery, Dabble Game